Effects of an educational video on the oral hygiene of patients with hematologic disorders - Emilia Campos de Carvalho; Ana Paula Neroni Stina; Milene Thaís Marmol; Livia Maria Garbin; Fernanda Titareli Merizio Martins Braga; Lucimara Moreli; Cristina Mara Zamarioli (Universidade Federal de Goias, 2014)
The current study aims at evaluating the effectiveness and acceptance of a video as a strategy for teaching oral hygiene to patients with hematologic disorders receiving chemotherapy. It is a quasi-experimental before and after study, composed of 23 subjects. After their routine oral hygiene routine was observed, patients watched a video about the procedure. Afterwards, the subjects carried out their oral hygiene once more. A paired student's t-test was used to compare the average of how many steps were performed correctly before and after the video presentation. Procedure performance was higher after watching the video (p <0.0001), being that the strategy was well accepted by patients. The oral hygiene video proved to be effective for the teaching of this procedure and was well accepted by patients. (ClinicalTrials.gov Identifier: NCT 01718002)   doi: 10.5216/ree.v16i2.23300.